Sounding out pain: a circuit for sound-induced analgesia has been found in the mouse brain - Kuner, Rohini; Kuner, Thomas (Science, 2022)
A circuit for sound-induced analgesia has been found in the mouse brain.
Gesehen am 04.08.2022